The Effect of Brandt Daroff Therapy on Rehabilitation in Vertigo Patients in Hospital Imelda Pekerja Indonesia Medan in 2017 - Arie Maineny; Taqwin Taqwin; Putri Mulia Sakti (Universitas Aisyah Pringsewu, 2021)
Brandt Daroff method is one form of physical therapy or physical exercise vestibular to overcome vestibular disorders such as vertigo. Physical therapy is done to adapt themselves to disturbance of balance, Brandt Daroff Therapy and Epley Maneuver therapy is a vestibular rehabilitation as therapy that can be done independently at home for patients with Benign Paroxysmal Positional Vertigo. Physiologically, Brandt Daroff plays a role in the adaptation of the vestibular system and the Epley Maneuver plays a role in autolytic repositioning. Of the fifty subjects studied over the group of Epley and Brandt-Daroff maneuvers, each group of 25 people. Both homogeneous groups in terms of sex, age after follow-up showed that Brandt-Daroff therapy was 50% better than Epley's epilepsy. The results of research published by the Secretariat Department of Neurology FKUI (2016). Can be a reference to the success of an action, intervention, treatment or therapy performed. Research identifies. The Influence of Brandt Daroff Therapy on Rehabilitation on Salted Vertigo at Hospital Imelda Pekerja Indonesian Medan. The research design used was quasi-experimental research. With this research design is One group pre–Test and Post-test. The study respondents consisted of 30 vertigo clients and were taken using a nonprobability sampling technique. Data collection using observation instrument VAS (Visual Analog Scale) with paired t-test technique Pretest and Post-test. The results of this study indicate the presence of contact between Brandt daroff therapy on rehabilitation in vertigo patients at Hospital Imelda Pekerja Indonesia Medan. Analysis of paired t-test pre–Test and Post-test showed that at the level of significance p = 0,5 in. Metode Brandt Daroff merupakan salah satu bentuk terapi fisik atau latihan fisik vestibuler untuk mengatasi gangguan vestibular seperti vertigo. Terapi fisik dilakukan untuk menyesuaikan diri terhadap gangguan keseimbangan, Terapi Brandt Daroff dan terapi Epley Maneuver merupakan rehabilitasi vestibular sebagai terapi yang dapat dilakukan secara mandiri di rumah bagi pasien Benign Paroxysmal Positional Vertigo. Secara fisiologis, Brandt Daroff berperan dalam adaptasi sistem vestibular dan Manuver Epley berperan dalam reposisi autolitik. Dari lima puluh subjek yang diteliti selama kelompok manuver Epley dan Brandt-Daroff, masing-masing kelompok 25 orang. Kedua kelompok homogen dalam hal jenis kelamin, usia setelah tindak lanjut menunjukkan bahwa terapi Brandt-Daroff 50% lebih baik daripada epilepsi Epley. Hasil penelitian diterbitkan oleh Sekretariat Departemen Neurologi FKUI (2016). Dapat menjadi acuan keberhasilan suatu tindakan, intervensi, pengobatan atau terapi yang dilakukan. Penelitian mengidentifikasi. Pengaruh Terapi Brandt Daroff Terhadap Rehabilitasi Vertigo Asin Di Rumah Sakit Imelda Pekerja Indonesia Medan Desain penelitian yang digunakan adalah penelitian eksperimen semu. Dengan desain penelitian ini adalah One group pre–Test Dan Post test. Responden penelitian terdiri dari 30 klien vertigo dan diambil dengan teknik nonprobability sampling. Pengumpulan data menggunakan instrumen observasi VAS (Visual Analog Scale) dengan teknik uji t berpasangan Pretest dan Post test. Hasil penelitian ini menunjukkan adanya kontak antara terapi Brandt daroff pada rehabilitasi pada pasien vertigo di Rumah Sakit Imelda Pekerja Indonesia Medan. Analisis uji t berpasangan pre-Test dan Post test menunjukkan bahwa pada taraf signifikansi p = 0,5.